Desain taman bermain anak berbasis daya kembang kognitif anak di Taman Kota Sewaka Dharma - Swastiani, Sari Yoga; Kohdrata, Naniek; Astawa, I Nyoman Gede (Jurnal Arsitektur Lansekap; Vol.8, No.2, Oktober 2022DO - 10.24843/JAL.2022.v08.i02.p03, 2022)
Denpasar City was awarded the Child-Friendly City award from 2011 to 2019. This achievement needs to be maximized by providing a children playground based on cognitive development, in order to facilitate children's development in the way of thinking and problem-solving. The purpose of this study is to map the existing condition and to create a children playground design based on cognitive development in Sewaka Dharma City Park. These research methods using inventory, analysis, synthesis, concept-making, planning, and design process. The site is divided into four playing spaces based on group age, that are 0-3 years, 3-6 years, 6-8 years, and 8-17 years age groups, each of which aimed to maximize cognitive development. Playground for group age of 0- 3 years is facilitated with sensory games, 3-6 years age with creative games, physical games for the 6-8 years age, and social games for the 8-17 years age. The design is not only adding playing equipments to the site, but also the designed playing facilities can contribute to users life quality based on their cognitive activity. The results of this research can be taken into consideration for further children playground development, so it does not only produce recreational facilities but can also improve the quality of human resources in the future.